2021
DOI: 10.33448/rsd-v10i11.18508
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic identification of bacteria of the family Enterobacteriaceae with resistance profile on inanimate surfaces in a University Hospital

Abstract: The aim of this study was to identify bacteria belonging to the family Enterobacteriaceae with resistance profile on inanimate surfaces and utensils of sectors from a University Hospital of Pernambuco. Initially, the samples were collected on 25 inanimate surfaces and utensils of the Intensive Care Unit (ICU), Hemodialysis Center and Medical Clinic in 2018. The samples were plated on MacConkey and SS agar and incubated at 35 ± 2 °C for 24 hours. After incubation, they were submitted to biochemical tests to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
1
2
1
Order By: Relevance
“…However, it is worth noting that the same survey reported a prevalence rate of 33.3% for ESBL-producing GNBs, which contrasts our study results [17]. Studies in Brazil have reported lower prevalence rates of ESBL-producing GNBs from contaminated hospital surfaces, e.g., 15.2% [15] and 24.8% [18]. Another study from Algeria [16] reported a prevalence rate of 21.4% for ESBL among GNBs isolated from the hospital environment.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…However, it is worth noting that the same survey reported a prevalence rate of 33.3% for ESBL-producing GNBs, which contrasts our study results [17]. Studies in Brazil have reported lower prevalence rates of ESBL-producing GNBs from contaminated hospital surfaces, e.g., 15.2% [15] and 24.8% [18]. Another study from Algeria [16] reported a prevalence rate of 21.4% for ESBL among GNBs isolated from the hospital environment.…”
Section: Discussioncontrasting
confidence: 98%
“…These findings highlight the potential role of fomites and human contact in transmitting antibiotic-resistant GNB within healthcare settings. This finding supports the well-established notion that GNBs, such as E. coli, P. aeruginosa, and Klebsiella pneumoniae, are responsible for nosocomial infection, especially among patients with extended hospitalization [14,15].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations